ANALISIS PENINGKATAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI DENGAN KETERLIBATAN RELAWAN PAJAK DALAM PELAPORAN SURAT PEMBERITAHUAN TAHUNAN (SPT) DI KPP PRATAMA MAKASSAR UTARA - Wahid, Jihan Zhalzabila; Sari, Ratna; Arsyad, Muhammad (Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2023)
This study aims to analyze the compliance of individual taxpayers (WPOP) in reporting their Annual Tax Return (SPT) with the involvement of tax volunteers, to identify the improvement in taxpayer compliance before and after the involvement of tax volunteers, and to evaluate the effectiveness of their role in SPT reporting at KPP Pratama Makassar Utara. The research employs a descriptive qualitative approach with data collected through interviews, observations, and documentation. Data analysis was conducted through data reduction, data presentation, and drawing conclusions and verification. The findings indicate that the involvement of tax volunteers plays a significant role in improving both formal and material compliance of individual taxpayers. Tax volunteers assist taxpayers in understanding reporting procedures, using the e-filing system, and providing tax education that enhances tax awareness